Intensified Medical Therapy Does Not Appear to Benefit Elderly Heart Failure Patients - Sylvester, Bruce (MD Conference Express, 2008)
Intensified NT-BNP (N-terminal B-type natriuretic peptide)-guided therapy is not more effective than standard, symptom-guided therapy in reducing death and all-cause hospitalization among elderly congestive heart failure patients, according to results from the Trial of Intensified [BNP-guided] versus standard [symptom-guided] Medical therapy in Elderly patients with Congestive Heart Failure [TIME-CHF; ISRCTN43596477].